The Role of Podcasts in the 2024 Political Campaigns Reviewed through the Perspective of Symbolic Interaction Theory - Habibah, Tiara Maulinda; Revolusi, Prabu (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The 2024 Indonesian election is a significant political event, with social media playing a crucial role in campaign communication and message conveying. Candidates and political parties use social media to garner support and mobilize voters, making campaigns more measurable and targeted. The Unpacking Indonesia Podcast, hosted by Zulfan Lindan, is a political discussion platform that invites various figures and analysts to discuss current issues in detail. The podcast features diverse speakers such as Hasan Nasbi, M. Qodari, Adi Prayitno, and Eros Djarot. Symbolic interaction theory, introduced by George Herbert Mead and Herbert Blumer, emphasizes the importance of symbols and social interaction in shaping social meaning and reality. In the context of the podcast